Application of the cost-benefit-benefit analysis in the evalutaion and selection of public projects (economic aspect - Petrović, Dragana N.; Đedović, Branko N.; Petrović, Nikola Č. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The cost-benefit-benefit analysis is a comprehensive analysis of benefits and cost-benefits of a project which that project brings to the project owner and to the society as a whole (including investors). The selection of the best investment alternative is realized on the basis of financial and economic analyses, as two integral parts of the cost-benefit-benefit analysis. The first of these was dealt by the same group of authors in the article „Application of the cost-benefit-benefit analysis in the evaluation and selection of public projects (financial aspect)“, published in the previous issue of the Military Technical Courier. The subject of this paper is the processing of an economic analysis as a logical extension of the previous work. Therefore, the number of labels included in the table of the financial analysis content (1-5) supplements (in the chronological order) label tables that belong to the economic analysis (6-8). The application of the economic analysis is achieved by a certain, quite complex procedure, and ends by establishing the basic criteria (indicators) of the economic (social) cost-benefit of the project, such as a net present value of cash flows and a cost-benefit-benefit ratio. The project is economically viable and socially justified for implementation if the first criterion is greater than zero, and the second criterion is greater than one. In the case of alternative choices, the project with the highest present value of cash flows and the highest value of the cost-benefit- benefit ratio will be selected. This paper processes all the issues regarding a gradual realization of the economic analysis in order to determine the economic viability of the project. Conversion of market prices to accounting prices The first question pointed out to the need of calculating the total cost-benefits and benefits into calculation (socially acceptable) prices, as a condition of the reality of the economic analysis. For the correction of current prices into accounting ones, the conversion factors or the limit prices of the CIF and FOB values are used. Monetization of non-market impacts The second question stresses the need for a monetary valuation of the project effects that cannot be assessed in the market. Among others, these effects include positive and negative external effects. Including additional indirect effects in the analysis The third issue deals with the analysis of direct and indirect effects. Direct effects (cost-benefits and benefits) are related to the achievement of projects. Indirect effects are the effects resulting from the realization of a project, and as such, they should be included in the economic analysis. Discounting estimated cost-benefits and benefits The subject of the analysis of the fourth question is discounting estimated cost-benefits and benefits. To determine the economic feasibility of the project, the cost-benefits and benefits of the project should be discounted, i.e.reduced to the first year planning period of the project, usng the total discount rate. Calculation of the indicators of the economic (social) returns of the project This Section starts from the assumption that a reasonable implementation of the project is the one whose total expected benefits exceed the total estimated cost-benefits. The economic viability of the project is evaluated by calculating the basis indicators of the social returns of the project, i.e. the net present value of cash flows and the cost-benefit-benefit ratio. Conclusion In conclusion, it was pointed out that the project is ecnonomically viable and socially jusitified for implementation if the first criterion (net present value of cash flow) is greater than zero and the other criterion (cost-benefit-benefit ratio) greater than one. In the case of alternative choices, the project with the highest present value of cash flows and the highest value of the cost-benefit- benefit ratio will be selected.